PERTANGGUNG JAWABAN PIDANA ATAS PENYALAHGUNAAN SENJATA API - Bayu Ariadi, Anak Agung Ngurah; Tjatrayasa, I Made; Walesa Putra, I Made (Kertha Wicara : Journal Ilmu Hukum, 2013)
Firearms are weapons that release one or more projectiles being driven athigh speed by the gas produced by the burning of a propellant. Criminal liabilityis defined as an objective the continuation of censure for criminal acts and theopinion that there is qualified to be convicted of the offense. Is the basis of theprinciple of legality of criminal acts, while the basic principle can judged themaker of crime is a principle of fault. This means that the makers of crime willonly be liable if he has a fault in committing it.
Keywords: Firearm, Criminal Responsibility